Prevalence, Pregnancy Outcomes and Treatment Modalities of Immune Thrombocytopenia Mothers Over 5-years in a Tertiary Health Care Hospital in South India - Shashikala Karanth; Christy Vijay; Chaitanya Harita; Jaya S. Mol (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
Background: It has been proposed that thrombocytopenia is the most common haematological abnormality in pregnancy after anaemia. The incidence of severe immune thrombocytopenia (ITP) in pregnancy has been difficult to report because of the rarity of the disease. Treating pregnancy associated with ITP can be difficult. Objective: The objectives were to determine the prevalence, pregnancy outcomes, and treatment modalities of ITP mothers over five years in a tertiary health care hospital in South India. Methods: Our study was a retrospective record study, which looked into various aspects of obstetrical outcomes and complications in ITP mothers. Records of the in-patient medical record department (MRD) folders of patients with ITP who delivered at St. Johns Medical Hospital, Bangalore were studied. Patients with acute and chronic ITP were included as per the Vicenza consensus conference and the criteria for differentiating primary from secondary forms of ITP was followed, with consideration of a new entity of ITP associated with the presence of antiphospholipid antibodies. Results: The study identified 53 patients with ITP with a mean age of 25.6+4.6 years, age of diagnosis of ITP at 21.1+5.9 years and gestational age of 36.2+3 weeks. In our study 17 (32%) were acute and 36 (67.1%) were chronic ITP. In our study, 39.6% had a history of at least one prior pregnancy loss. Patients with ITP at 35-37 weeks were induced with PGE1 (35.7%) in comparison to those with PGE2 (p\(\)0.001). Post-partum haemorrage (PPH) was seen in 7.5% of the pregnancies and all four were mothers with chronic ITP. Severe preeclampsia in ITP mothers was seen in 2 (66.7%). All the findings showed that there is no reliable maternal parameter to predict the susceptibility and the need for intervention in mothers with life-threatening thrombocytopenia and the complications it poses to the foetus. Hence, constant vigilance is required to establish a safe pregnancy outcome in mothers with ITP. Conclusions: Chronic ITP in pregnancy poses more risks to mother and foetus as seen with the higher chance of PPH etc. Mothers with ITP should be screened antenatally as the chances of anomalies are high in the foetus.